Anthelmintic Potential of Conjugated Long-Chain Fatty Acids Isolated from the Bioluminescent Mushroom Neonothopanus gardneri - Oliveira, Maria D A; Dos S Andrade, Teresinha de Jesus A; Junior, Joaquim S C; Lima, Nerilson Marques; Machado, Hugo G.; Tabudravu, Jioji N.; Pinto, Francisco das Chagas L; Fukui-Silva, Lucas; Amaro, Monique C.; de Moraes, Josué; Silva, Dulce Helena S [UNESP]; Citó, Antônia Maria das Graças L; et al. (American Chemical Society (ACS), 2025)
With praziquantel being the sole available drug for schistosomiasis, identifying novel anthelmintic agents is imperative. A chemical investigation of the fruiting body of the bioluminescent mushroom Neonothopanus gardneri Berk. resulted in the isolation of new conjugated long-chain fatty acids (8E,10E,12S,13S)-12,13-dihydroxy-7-oxo-octadeca-8,10-dienoic acid (1) and (7S,8S,9E,11E)-7,8-dihydroxy-13-oxo-octadeca-9,11-dienoic acid (2) and three previously described compounds, (7R,8R,9Z)-7,8-dihydroxyoctadec-9-enoic acid (3), (2E)-dec-2-ene-1,10-dioic acid (4), and a ketolactone marasmeno-1,15-dione (5). Their planar structures were elucidated based on 1D and 2D NMR and MS/MS spectroscopic analyses. Compound 3 displayed significant antiparasitic activity against Schistosoma mansoni ex vivo (EC50 < 10 μM). No toxicity was observed in mammalian cells or Caenorhabditis elegans.